Colony dispersion and nesting habits of the ants, Dolichoderus thoracicus and Oecophylla smaragdina (Hymenoptera: Formicidae), in relation to their success as biological control agents on cocoa - Way, M. J.; Khoo, K. C. (Cambridge University Press, 1991)
In mixed cocoa-coconut palm plantations in Malaysia the palm spadices provide large, stable nesting sites for Dolichoderus thoracicus (Smith) in contrast to impermanent sites on cocoa and on the ground. D. thoracicus and the arboreal leaf-nesting Oecophylla smaragdina (Fabricius) both benefit from the mixed system which also provides a more stable food supply from honeydew-producing Homoptera. A scoring method showed that about 50–200 O. smaragdina or 200–2000 D. thoracicus on a cocoa tree can protect it effectively from Helopeltis theobromae Miller (Hemiptera: Miridae). The relatively greater efficiency of O. smaragdina as a biological control agent is associated with its actively dispersive predatory behaviour in contrast to the localized concentration of D. thoracicus workers at sites such as cocoa pods where it tends honeydew-producing Homoptera, and where it acts largely by deterring H. theobromae. Despite its biological control potential, the painfully biting O. smaragdina, unlike D. thoracicus, is normally considered unacceptable to plantation staff. Nevertheless it should be recognized as valuable in integrated pest management of cocoa pests especially where D. thoracicus is difficult to establish.